Lithium polysulfide and sulfide solid electrolyte containing lithium polysulfide
By preparing lithium polysulfides through a stepwise ball milling process and supplementing sulfur in situ into the sulfide solid electrolyte, the problems of sulfur volatilization and component segregation were solved, resulting in a high-purity and high-performance sulfide solid electrolyte suitable for core materials in solid-state batteries.
Patent Information
- Application Number
- CN202511160566.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-12-02
AI Technical Summary
In the existing technology, the decomposition of phosphorus pentasulfide during the high-temperature sintering process of sulfide solid electrolytes leads to the volatilization of sulfur, resulting in the loss of sulfur in the electrolyte, component segregation, and poor batch stability, which makes it difficult to meet the requirements of large-scale production. At the same time, the uneven distribution of elemental sulfur during calcination and the difficulty in storing and transporting hydrogen sulfide gas affect the industrialization process.
Lithium polysulfides were prepared using a stepwise ball milling process. By controlling the molar ratio of lithium nitride to sulfur powder and adding it stepwise, lithium polysulfides containing short-chain Li2S2/Li2S3 and long-chain Li2S6/Li2S8 components were generated. When preparing sulfide solid electrolytes, elemental sulfur was released by heating and decomposing lithium polysulfides, and sulfur was added in situ to avoid elemental segregation.
This invention achieves high purity and high room temperature ionic conductivity in sulfide solid electrolytes, solves the problems of sulfur volatilization and component segregation, and improves batch stability and electrolyte performance.
Smart Images

Figure CN121044546A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sulfide electrolyte technology, specifically to lithium polysulfides and lithium polysulfide-containing solid sulfide electrolytes. Background Technology
[0002] Sulfide solid electrolytes have become the core material for solid-state batteries due to their room-temperature ionic conductivity, which is close to that of liquid electrolytes. Currently, the mainstream preparation method is ball milling followed by solid-phase sintering. However, during the high-temperature sintering process, the decomposition of phosphorus pentasulfide leads to the volatilization of elemental sulfur, resulting in problems such as sulfur deficiency in the electrolyte, component segregation, and poor batch stability, which seriously restricts large-scale production.
[0003] CN120004221A discloses a method for preparing high-purity lithium sulfide, relating to the field of battery manufacturing technology. The method includes the following steps: preparing high-purity sulfur powder; lithium hydride pretreatment; proportioning and feeding; high-speed ball milling; room temperature cooling; ball milling detection; and collection and packaging. This method for preparing high-purity lithium sulfide, by filling the ball mill jar with argon gas, ensures that the reaction between lithium hydride and high-purity sulfur powder is always carried out under the protection of argon gas. This not only guarantees the safety of the reaction but also reduces the use of toxic gases during lithium sulfide production, ensuring both efficiency and safety in the production process. Simultaneously, a rotary furnace at the bottom of the ball mill jar drives the jar to rotate continuously, ensuring sufficient and uniform heating of both lithium hydride and high-purity sulfur powder. This method relates to the preparation of pure-phase lithium sulfide.
[0004] Existing sulfur source replenishment methods suffer from uneven distribution due to the molten state of elemental sulfur during calcination, and hydrogen sulfide gas presents challenges in storage and transportation, as well as low reaction efficiency. These deficiencies fail to meet the requirements of industrial production for uniform sulfur source and process stability. Furthermore, sulfide electrolytes face challenges such as poor air stability (easily reacting with water to form highly toxic hydrogen sulfide), high energy consumption in traditional solid-phase methods, and difficulties in solvent recovery in liquid-phase methods, further limiting their industrialization. Therefore, developing a preparation technology that achieves uniform sulfur source replenishment while balancing process safety and cost-effectiveness is crucial to overcoming the bottlenecks in the large-scale application of sulfide solid electrolytes. Summary of the Invention
[0005] Therefore, the object of the present invention is to provide a lithium polysulfide and a lithium polysulfide-containing sulfide solid electrolyte thereof. This object is achieved through the following technical solution:
[0006] First aspect: A method for preparing lithium polysulfide, comprising the following steps:
[0007] S1. Preparation of lithium nitride using metallic lithium as the lithium source;
[0008] S2. Weigh the raw materials according to the molar ratio of lithium nitride to sulfur powder of 2:3 to 3.3, divide the lithium nitride into 2 to 4 equal parts, and prepare lithium sulfide by stepwise ball milling under a dry inert atmosphere.
[0009] In step S2, the stepwise ball milling process includes: adding sulfur powder and the first portion of lithium nitride into a ball milling container equipped with a pressure regulating device, and ball milling at a speed of 400-550 rpm for 2-3 hours; then adding one portion of lithium nitride every 2-3 hours, and continuing ball milling for 2-3 hours after all the lithium nitride has been added.
[0010] In step S1, the lithium metal is a lithium strip with a thickness of 0.2 mm to 5 mm, which reacts under a nitrogen atmosphere to generate lithium nitride sheets, which are then pulverized and refined to a particle size of 50-100 μm.
[0011] In step S2, the pressure regulating device is a one-way exhaust valve; the ball-to-material ratio is 10-15:1. (The one-way valve can automatically exhaust air when the pressure reaches the threshold to prevent the pressure inside the tank from becoming too high; at the same time, it prevents external air from entering in reverse and maintains an inert atmosphere).
[0012] Preferably, in step S2), the lithium nitride is divided into three equal portions, and the total ball milling time is 7-8 hours. The reaction equation for the ball milling process is 2Li3N + 3nS → 3Li2S n +N2↑,Li2S n +S +Li3N→Li2S +Li2S n +N2↑. Furthermore, due to the gas production from the reaction, the exhaust valve of the ball mill must be kept open during the ball milling process; otherwise, the nitrogen gas generated during the reaction will undergo a side reaction with the unreacted elemental sulfur under high temperature and pressure, forming unstable sulfur-nitrogen compounds, which pose an explosion risk.
[0013] Secondly, the present invention provides a lithium polysulfide prepared by the preparation method described above.
[0014] Thirdly, the present invention provides a method for preparing a sulfide solid electrolyte, comprising the following steps:
[0015] 1) Mix lithium polysulfides, phosphorus sulfides and lithium chloride (LiCl), and then ball mill for hours;
[0016] 2) Press the ball-milled mixture into tablets and hold at 480-500℃ for 1-2 hours under an inert atmosphere to obtain the silver-germanium sulfide solid electrolyte Li. 5.5 PS 4.5 Cl 1.5 .
[0017] The mass ratio of lithium polysulfide, phosphorus pentasulfide, and lithium chloride is 93:112.5:64.4.
[0018] In step 1), the ball-to-material ratio is 15-20:1, and the ball mill speed is 400-500 rpm / min.
[0019] The phosphorus sulfide includes phosphorus pentasulfide (P2S2).
[0020] In step 2), the inert atmosphere is nitrogen or argon, and the tableting pressure is 5-10 MPa.
[0021] Fourthly, the present invention provides a sulfide solid electrolyte of silver-germanium sulfide type prepared by the preparation method described above.
[0022] The lithium polysulfide powder of the present invention is prepared by a stepwise ball milling process and contains short-chain Li2S2 / Li2S3 and long-chain Li2S6 / Li2S8 components.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0024] 1. In existing technologies, lithium sulfide is mainly prepared using a two-step method: first, lithium nitride is prepared, and then it reacts with elemental sulfur to obtain lithium sulfide. In this invention, a specific process is used to incorporate a portion of lithium polysulfides into the lithium sulfide preparation. Lithium polysulfides gradually decompose at 200-400℃. Short-chain Li₂S₂ / Li₂S₃ decomposes at higher temperatures, above 300℃, while long-chain Li₂S₆ / Li₂S₈ decomposes at lower temperatures, starting around 200℃, generating lithium sulfide and sulfur vapor.
[0025] 2. This invention employs a stepwise ball milling process. Elemental sulfur is weighed according to a lithium nitride to sulfur powder molar ratio of 2:3-3.3, and lithium nitride is divided into 2-3 equal portions for later use. Under a dry, inert atmosphere, sulfur powder and one portion of lithium nitride are added to a stainless steel ball mill jar equipped with an exhaust valve for ball milling. Subsequently, one portion of lithium nitride powder is added every two hours. After all the powder has been added, ball milling continues for two hours to ensure complete reaction. This stepwise addition of lithium nitride allows the lithium nitride to contain a portion of lithium polysulfides.
[0026] 3. In the preparation of sulfide solid electrolytes, traditional methods require the addition of an external sulfur source to suppress sulfur volatilization due to the decomposition of phosphorus pentasulfide and the volatilization of sulfur during calcination. However, the addition of external sulfur sources (such as elemental sulfur and hydrogen sulfide) presents several problems. For example, elemental sulfur has poor practical performance in its molten state during calcination, and hydrogen sulfide gas is difficult to store and transport. During large-scale preparation, it cannot effectively participate in the reaction to replenish the lost sulfur within the electrolyte and is prone to causing component segregation, affecting batch stability. This invention uses lithium sulfide materials containing lithium polysulfides to prepare sulfide solid electrolytes. The process of lithium polysulfides decomposing upon heating and releasing elemental sulfur replenishes the lost elemental sulfur in situ during the solid-phase sintering reaction of the electrolyte, preventing elemental segregation during electrolyte sintering. Simultaneously, some lithium polysulfides are retained and directly enter the electrolyte crystal through the solid-phase reaction to improve electrolyte performance, effectively solving the problems of sulfur loss and component segregation in existing technologies. Attached Figure Description
[0027] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:
[0028] Figure 1 The XRD pattern of the lithium polysulfide sample in Example 1;
[0029] Figure 2 XRD pattern of the sulfide solid electrolyte in Example 1;
[0030] Figure 3 The Raman spectrum of lithium polysulfide prepared in Example 1;
[0031] Figure 4 The image shows the Raman spectrum of lithium sulfide prepared for Comparative Example 1. Detailed Implementation
[0032] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.
[0033] Example 1
[0034] This embodiment prepares a high-purity lithium sulfide material, and the specific steps are as follows:
[0035] Step 1: Preparation of Lithium Nitride
[0036] In a nitrogen atmosphere glove box, take 30g of lithium metal strip, remove the surface oxide layer with a steel brush, and let it stand until the reaction is complete to obtain lithium nitride sheet (mass 50g).
[0037] Step 2: Crushing and Sampling of Lithium Nitride
[0038] The lithium nitride sheets were pulverized and then ball-milled to a particle size of less than 100 μm, and then evenly divided into 3 equal portions (each portion weighing approximately 16.67 g).
[0039] Step 3: Preparation of lithium polysulfides
[0040] Phase 1: Initial ball milling
[0041] Place one portion of lithium nitride powder (approximately 16.67 g) into a stainless steel ball mill jar equipped with an exhaust valve, add 70 g of elemental sulfur, set the ball mill speed to 500 rpm, and the ball-to-material ratio to 15:1; after sealing, start the ball mill and continue for 2 hours.
[0042] Phase 2: Secondary feeding and ball milling
[0043] After the first ball milling, open the can and add the second portion of lithium nitride powder (approximately 16.67g). Keep the ball milling speed constant at 550 rpm and continue ball milling for 2 hours.
[0044] Phase 3: Three Feeding Stages and Final Ball Milling
[0045] After the second ball milling, the third portion of lithium nitride powder (approximately 16.67 g) was added, and ball milling continued for 3 hours at the same speed to ensure complete reaction. After the reaction was completed, the product was removed and sieved to obtain 96.4 g of lithium polysulfide powder. The XRD pattern of the prepared lithium polysulfide sample is shown below. Figure 1 As shown; Raman spectra are as follows Figure 3 As shown.
[0046] Weigh 93g of the above lithium polysulfide powder, 112.5g of phosphorus pentasulfide (P2S5) and 64.4g of lithium chloride (LiCl), mix them and ball mill for 3 hours; ball mill speed 500 rpm / min.
[0047] The ball-milled mixture was pressed into tablets and held at 480°C for 2 hours under an inert atmosphere (nitrogen or argon, pressing pressure 5–10 MPa) to obtain the silver-germanium sulfide solid electrolyte Li. 5.5 PS 4.5 Cl 1.5 The XRD pattern of the prepared sulfide solid electrolyte is shown below. Figure 2 As shown.
[0048] This embodiment controls the reaction process through stepwise ball milling, optimizes the material ratio and heat treatment conditions, and can stably prepare high-purity sulfide solid electrolyte materials.
[0049] Example 2
[0050] The operation in this embodiment is the same as in embodiment 1, except that the ball milling speed in stage 1 is set to 400 rpm / min, and 97.7 g of lithium sulfide powder is finally obtained.
[0051] Example 3
[0052] The operation in this embodiment is the same as in embodiment 1, except that lithium nitride is added in four parts to finally obtain 98.1g of lithium sulfide powder.
[0053] Comparative Example 1
[0054] The operation in this embodiment is the same as in Example 1, except that lithium nitride is added all at once. The Raman spectrum of the prepared lithium sulfide is as follows. Figure 4 As shown.
[0055] Performance testing
[0056] The sulfide solid electrolyte materials prepared in each embodiment and comparative example were subjected to ionic conductivity tests.
[0057] Test methods: X-ray diffraction was used to test the crystal structure of the material, and Raman spectroscopy was used for qualitative analysis of lithium sulfide and lithium polysulfide in the material. A sulfosilver-germanium ore-type electrolyte, Li, was synthesized. 5.5 PS 4.5 Cl 1.5 A comparison of the quality of lithium sulfide was conducted.
[0058] Test results:
[0059] Table 1 Comparison of test data results for each embodiment
[0060]
[0061] This application, by introducing lithium polysulfide components and employing a stepwise ball milling process, prepares a sulfide solid electrolyte with higher purity and room-temperature ionic conductivity. The ionic conductivities of the sulfide solid electrolytes prepared in Examples 1-3 are 10.4 mS / cm, 9.7 mS / cm, and 10.7 mS / cm, respectively, while the ionic conductivity of Comparative Example 1 (where all lithium nitride is added at once) is 8.6 mS / cm. This indicates that the method of this invention can significantly improve the performance of the sulfide solid electrolyte and has a clear technical advantage compared to Comparative Example 1.
[0062] It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the substantive content of the present invention.
Claims
1. A method for preparing lithium polysulfide, characterized in that, Includes the following steps: S1. Preparation of lithium nitride using metallic lithium as the lithium source; S2. Weigh the raw materials according to the molar ratio of lithium nitride to sulfur powder of 2:3~3.3, divide the lithium nitride into 2~4 equal parts, and prepare lithium sulfide by stepwise ball milling under a dry inert atmosphere. In step S2, the stepwise ball milling process includes: adding sulfur powder and the first portion of lithium nitride into a ball milling container equipped with a pressure regulating device, and milling at a speed of 400~550 rpm for 2-3 hours; then adding one portion of lithium nitride every 2-3 hours while keeping the ball milling speed constant, and continuing to mill at a speed of 400~550 rpm for 2-3 hours after all the additions are completed.
2. The method according to claim 1, characterized in that, In step S1, the lithium metal is a lithium strip with a thickness of 0.2 mm to 5 mm, which reacts under a nitrogen atmosphere to generate lithium nitride sheets, which are then pulverized and refined to a particle size of 50-100 μm.
3. The method according to claim 1, characterized in that, In step S2, the pressure regulating device is a one-way exhaust valve; the ball-to-material ratio is 10-15:
1.
4. The method according to claim 1, characterized in that, In step S2, lithium nitride is divided into 3 equal parts, and the total ball milling time is 7-8 hours.
5. Lithium polysulfide prepared by any one of claims 1-4.
6. A method for preparing a sulfide solid electrolyte, characterized in that, Includes the following steps: 1) The lithium polysulfide, phosphorus sulfide and lithium chloride as described in claim 5 are mixed and then ball-milled for hours; 2) Press the ball-milled mixture into tablets and hold at 480-500℃ for 1-2 hours under an inert atmosphere to obtain the silver-germanium sulfide solid electrolyte Li. 5.5 PS 4.5 Cl 1.5 .
7. The preparation method according to claim 6, characterized in that, The mass ratio of lithium polysulfide, phosphorus pentasulfide, and lithium chloride is 93:112.5:64.
4.
8. The preparation method according to claim 6, characterized in that, In step 1), the ball-to-material ratio is 15-20:1, and the ball mill speed is 400-500 rpm / min.
9. The preparation method according to claim 6, characterized in that, The phosphorus sulfide includes phosphorus pentasulfide.
10. The sulfide solid electrolyte of silver-germanium ore type prepared by the preparation method according to any one of claims 6-9.
Citation Information
Patent Citations
Preparation method of high-purity lithium sulfide
CN120004221A
Method for synthesizing sulfide solid electrolyte
CN112768760A
Preparation method of solid electrolyte
CN113437357A
Preparation method of lithium sulfide
CN116216652A
Lithium sulfide and preparation method and application thereof
CN119240619A